2019
DOI: 10.1111/hsc.12767
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress, resilience, and health‐related quality of life among Parkinson's disease caregivers in Mexico

Abstract: The stress process model of caregiving posits that caregivers' internal psychosocial resources may serve as buffers between the stress associated with caregiving and well‐being. Empirical support for the stress process model exists for several caregiving contexts, but little research has investigated the Parkinson's disease caregiving experience in Mexico. Using a cross‐sectional, correlational design, the objective of this study was to examine whether resilience moderates the relation between perceived stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 50 publications
(61 reference statements)
2
20
0
Order By: Relevance
“…Resilience is thought to be a positive protective factor that enables caregivers of patients with chronic disease to maintain stability when confronted with care‐related distress. Also, resilience has a positive impact on mental well‐being outcomes, 45 as confirmed with the results of the present study. Therefore, caregivers with a high level of resilience are more likely to accept and deal with serious psychological harm.…”
Section: Discussionsupporting
confidence: 91%
“…Resilience is thought to be a positive protective factor that enables caregivers of patients with chronic disease to maintain stability when confronted with care‐related distress. Also, resilience has a positive impact on mental well‐being outcomes, 45 as confirmed with the results of the present study. Therefore, caregivers with a high level of resilience are more likely to accept and deal with serious psychological harm.…”
Section: Discussionsupporting
confidence: 91%
“…A severe dependence level due to the care receiver's pathologies, the heavy physical, psychological, and emotional demands of the act of caring, and any changes in the caregiver's dimensions cause anguish. However, this condition significantly reduces when promoting resilience (32)(33)(34). Literature focuses on informal or family caregivers' resilience, especially when taking care of people with dementia ( 35) and Alzheimer's disease (36)(37), and their high depression, anxiety, hopelessness, emotional burden, stress, and anguish levels.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of suicidal ideation in PD patients ranged from 10.2% ~ 14.4% 20 , 21 . Furthermore, few studies that have detected fatigue 15 , 24 , resilience 25 , 26 , and suicidal ideation 27 among caregivers of PD patients. One study demonstrated that caregivers of PD patients experienced daily physical health problems including: muscle strain, headaches, and fatigue (17%) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that caregivers of PD patients experienced daily physical health problems including: muscle strain, headaches, and fatigue (17%) 24 . One study found that resilience modulated the inverse relation between perceived stress and QOL 25 . Furthermore, resilience partially influenced the effects of social support on the mitigation of mental health symptoms 26 .…”
Section: Introductionmentioning
confidence: 99%